Antifungal action of essential oils on Colletotrichum musae in vitro - Rezende, Dalilla Carvalho; José Galvão Chagas, Yuri; Perez de Carvalho, Hebe; Fagundes de Carvalho, Beatriz; Vilar Fernandes, Ítalo; Perez de Carvalho dos Santos, Ana Carolina (Revista Agrogeoambiental, 2022)
Anthracnose is a phytosanitary problem affecting banana producers. It is a major postharvest disease and is mainly controlled by the use of fungicides. As the search for healthy foods free of chemical residues has increased among consumers, the objective of this study was to evaluate the in vitro antifungal efficacy of different concentrations of essential oils on mycelial growth of Colletotrichum musae, the causal agent of anthracnose in banana fruits. The essential oils used were citronella grass (Cymbopogon nardus), lemongrass (Cymbopogon citrates), clove (Syzygium aromaticum), and basil (Ocimum basilicum). The essential oils were added to a potato dextrose agar medium at concentrations of 0, 0.5, 1.0, 1.5, 2.0,and 2.5 μLmL−1 and distributed in 90 mm diameter Petri dishes. Mycelium discs from the fungal colony, grown for seven days, were transferred to Petri dishes containing the oils and incubated at 25°C with a photoperiod of 12 h (light/dark) cycle for eight days. Colony growth was monitored daily to determine the percentage, index of inhibition of mycelial growth, and average diameter of the colonies. The experimental design consisted of randomized blocks with six different extract concentrations with replicates (n = 4). Each oil extract was then evaluated separately. The essential oils from citronellagrass, lemongrass, and basil inhibited mycelial growth to the proportion that the oil concentration increased. The total inhibition of the pathogen occurred at a concentration of 1.5 µLmL−1 using citronellagrass and lemongrass and 2.5 µLmL−1 using basil. However, essential oils from clove completely inhibited the mycelial growth of C. musae at a concentration of 0.5 µLmL−1. The tested essential oils showed in vitro antifungal activity against C. musae at different concentrations. However, essential oils from clove are unique in exhibiting a better inhibitory effect on mycelial growth at lower concentrations.